Pengaruh Kebijakan Hutang, Profitabilitas dan Ukuran Perusahaan terhadap Nilai Perusahaan dengan Kebijakan Dividen sebagai Variabel Moderasi - Nickyta Emilia Putri; Mu'minatus Sholichah (Journal of Culture Accounting and Auditing, 2023)
The research aims to determine the effect of debt policy, profitability and firm size on firm value with dividend polici as moderating variable. The method used is quantitative with secondary data in the form of a complete annual financial report of the company. The population used is infrastructure, transportation, logistics, technology, property & real estate and finance companies for the period 2018 – 2019. The research sample amounted to 44 samples using purposive sampling technique. The data analysis technique used multiple linear regression and Moderated Regression Analysis (MRA) test to test the moderating role of dividend policy. The results showed that debt policy and profitability had no effect on firm value. While the firm size has a significant effect on firm value. The result of the Moderated Regression Analysis (MRA) with dividend policy show that the interaction of dividend policy cannot moderate the relationship between debt policy and firm size with no effect on firm value. While the interaction of dividen policy can moderate (strengthen) the relationship of the profitability with a positive effect on firm value.